(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
In the article on the basis of analysis and generalization of the research outcomes of the author and different other researchers, some geographical features and development regularities of rural areas and settlements distribution in mountainous countries are worked out.